Fracture Prediction in Weldox 700E Steel Subjected to High Velocity Impact Using LS-DYNA - Nikesh Kumar Ojha; Ravindra K. Saxena; Govind Vashishtha; Sumika Chauhan (Applied Sciences)
Analyzing fracture behaviour during high-velocity impacts is critical for designing and developing structures in various scientific and technological fields. This study investigates the fracture behaviour of Weldox 700E steel plates with varying values of fracture parameters and fracture strain criteria using LS-DYNA/explicit. It also discusses the effect of varying plate thicknesses (2 to 6 mm) when impacted by a blunt-nosed projectile with varying masses and varying velocities. The fracture behaviour of flat steel target plates is analyzed with a focus on fracture variables across the top, mid, and bottom elements of the plate thickness. It is observed that the higher value of the fracture parameter results in a smooth fracture surface with Johnson–Cook (JC) fracture strain criteria. For thicker plates, both strain rate and temperature significantly affect the process, while for thinner plates, strain rate predominantly determines element deletion. The results reveal that for the top elements, equivalent plastic strain is the dominant factor causing failure at higher velocities, while temperature plays a significant role at lower velocities. For the mid elements, both plastic strain rate and temperature are critical, whereas for the bottom elements, equivalent plastic strain, plastic strain rate, and temperature are the primary factors. In all cases, shear-type fracture is consistently observed along the mid element of the target plate.